The role of AI and digital technologies in shaping a safe environment - Davyd Hrytsenok; Larysa Tereminko; Теремінко Лариса (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. In recent years, the integration of artificial intelligence (AI) and digital technologies has significantly transformed the way societies approach safety, security, and sustainability. The rapid growth of computational power, machine learning algorithms, and smart data systems has enabled the creation of intelligent environments that not only respond to threats but also predict and prevent them. The relevance of this topic lies in the increasing reliance of critical infrastructure, transportation, healthcare, and urban management on intelligent digital solutions that ensure human and environmental safety. The 21st century is characterized by the digitalization of nearly every aspect of human life. Technologies such as the Internet of Things (IoT), big data analytics, and AI-driven automation play a key role in creating safe and resilient systems. The global shift toward “smart” technologies has enabled the detection of natural disasters, the identification of cybersecurity threats, and the real-time monitoring of public spaces. These capabilities are essential for modern societies, especially in contexts where security risks evolve rapidly.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: digital technologies; environmental safety